2014
DOI: 10.5395/rde.2014.39.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Pull-out bond strength of a self-adhesive resin cement to NaOCl-treated root dentin: effect of antioxidizing agents

Abstract: ObjectivesThis study evaluated the effect of three antioxidizing agents on pull-out bond strengths of dentin treated with sodium hypochlorite.Materials and MethodsRoot canals of 75 single-rooted human teeth were prepared. Fifteen teeth were irrigated with normal saline for a negative control group, and the remaining 60 teeth (groups 2 - 5) with 2.5% NaOCl. The teeth in group 2 served as a positive control. Prior to post cementation, the root canals in groups 3 - 5 were irrigated with three antioxidizing agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…In addition, the present study showed that use of 10% sodium ascorbate for 10 minutes on the dentin treated with 5.25% NaOCl significantly increased the bond strength of both all-in-one adhesive systems. In previous studies, too, the positive and significant effect of the use of 10% sodium ascorbate has been shown in increasing the bond strength of etch-and-rinse ( 6 , 7 ) and self-adhesive cements ( 29 ) to dentin treated with NaOCl. Based on the results of a study by Vongphan et al ( 14 ) the effect of sodium ascorbate on increasing the bond strength was predominantly attributed to chemical reactions.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the present study showed that use of 10% sodium ascorbate for 10 minutes on the dentin treated with 5.25% NaOCl significantly increased the bond strength of both all-in-one adhesive systems. In previous studies, too, the positive and significant effect of the use of 10% sodium ascorbate has been shown in increasing the bond strength of etch-and-rinse ( 6 , 7 ) and self-adhesive cements ( 29 ) to dentin treated with NaOCl. Based on the results of a study by Vongphan et al ( 14 ) the effect of sodium ascorbate on increasing the bond strength was predominantly attributed to chemical reactions.…”
Section: Discussionmentioning
confidence: 93%
“… 18 , 19 The effects of Rosmarinic acid (RA) and hesperidin (HES) as antioxidants for post surface treatment have been investigated in different studies. 20 , 21 RA contains p-toluenesulfinic acid sodium salt and it was shown that application of RA for 30 seconds can improve the bond strength of resin adhesives to NaOCl-treated dentin. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Others have reported that the diameters of the "punch pins" in all tests were in accordance with the size of samples and induced a load from apical to the coronal direction on the post without applying any pressure over cement and/or over dentin [85,146,[149][150][151][152][153][154][155][156][157][158]. All ensured that the force was properly applied.…”
Section: Load Typementioning
confidence: 98%